1988
DOI: 10.1073/pnas.85.22.8693
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Epstein-Barr virus by allogeneic bone marrow transplantation: implications for sites of viral latency.

Abstract: Wild-type strains of Epstein-Barr virus (EBV) can be distinguished on the basis of variations in the molecular weight of virus-encoded, growth transformationassociated proteins. This approach was used to study the persistence of EBV in two seropositive recipients of allogeneic bone marrow transplants. The first patient received marrow from her EBV-seronegative brother, became EBV seronegative after grafting, and remained so for >1200 days. Subsequently, she became infected with a new EBV strain that differed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
102
0
2

Year Published

1989
1989
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(110 citation statements)
references
References 31 publications
5
102
0
2
Order By: Relevance
“…Latency is established in small B-lymphocytes, with lytic infection rarely detected in oral epithelium. 17,18 In the present study, EBV as expected was detected in all eight cases within numerous tissues, most prominently hematolymphoid tissues (lymph node, spleen, tonsil, thymus, bone marrow, blood), pharyngeal tissues (tongue, parotid gland), and digestive tissues (esophagus, stomach, small intestine, large intestine, liver, pancreas).…”
Section: Discussionsupporting
confidence: 77%
“…Latency is established in small B-lymphocytes, with lytic infection rarely detected in oral epithelium. 17,18 In the present study, EBV as expected was detected in all eight cases within numerous tissues, most prominently hematolymphoid tissues (lymph node, spleen, tonsil, thymus, bone marrow, blood), pharyngeal tissues (tongue, parotid gland), and digestive tissues (esophagus, stomach, small intestine, large intestine, liver, pancreas).…”
Section: Discussionsupporting
confidence: 77%
“…Accordingly, the work calls into question earlier models of EBV persistence, which envisaged latent infection being maintained within the basal epithelial compartment (Rickinson et al, 1985;Allday & Crawford, 1988), and refocuses attention on the B lymphoid system as a reservoir of latent EBV. Similarly, results from two other recent studies of the EBV carrier state stress the importance of B cells as a site of virus persistence (Gratama et al, 1988 ;Yao et al, 1989 a, b). If HL does indeed represent a focus of self-sustained virus replication, how might this be achieved in the absence of latent infection in the underlying basal layer?…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have found that the haematopoetic compartment is probably responsible for long-term viral persistence (Gratama et al, 1988). The normal precursor of the BL cell is a likely candidate for this role.…”
Section: Discussionmentioning
confidence: 99%